The Level of Education, Knowledge, Attitudes and Acceptance of the Covid-19 Vaccine in the North Sulawesi Community - Lolong, Rima Fien; Rawis, Joulanda A.M.; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree; Welong, Krety Debora (JR Education, 2023)
Corona Virus Disease (Covid)-19 is still a global problem. One of the efforts in the health sector to control this disease is vaccination. However, several problems were encountered in carrying out vaccination activities such as low education, lack of knowledge, and negative attitudes towards the Covid-19 vaccine. The purpose of this study was to analyze the correlation between education level, knowledge and attitudes, and acceptance of Covid-19 vaccination in the North Sulawesi community. This is observational research with a cross-sectional approach. This research was carried out in North Sulawesi Province by taking the focus on the place, namely in Minahasa Regency. This research was conducted in December 2022. The respondents to this study were 400 people aged 18 years and over who were willing to be respondents. The sampling method used is accidental sampling. The variables in this study are the level of education, knowledge, attitude, and acceptance of the Covid-19 vaccination. The instrument used is a questionnaire that has been tested for validity and reliability. Data was obtained through interviews with respondents. Interviews were conducted online (using the Google form) and offline (conducted directly in the community). Data analysis was carried out in this study using the chi-square test. The results showed that the correlations between education level and vaccination acceptance found a value of p = 0.014 (p <0.05), which means that education level was significantly correlated to vaccination acceptance. In addition, a PR value of 1.989 was obtained, which means that respondents with low education were more likely to receive incomplete vaccinations 1.989 times. The correlations between knowledge and vaccination acceptance found a p-value of 0.435 (p> 0.05), which means that knowledge had no significant correlations with vaccination acceptance. The correlations between attitude and vaccination acceptance found a p-value of 0.012 (p <0.05), which means that attitude is significantly correlated to vaccination acceptance. In addition, a PR value of 2.111 was obtained, which means that respondents who had a poor attitude 2.111 times more easily received incomplete vaccinations. It can be concluded that the level of education and attitude were factors correlated to the acceptance of the Covid-19 vaccination in the North Sulawesi community.